(untitled) (Advancements in Homeopathic Research, 2025)
Background: In today’s world, lumbago is one of the most prevalent and debilitating diseases. It is a disease condition, which is statistically recorded to seek medical attention second only to common cold. It mainly affects muscles, nerves and bones of the back in between the bottom fold of the buttocks and lower edge of the ribs. Globally, lumbago has been ranked 13th in disability adjusted life-years in the year 2010. Non-steroidal anti-inflammatory drugs (NSAIDs) and paracetamol both significantly lessen the pain. However, they shouldn’t be used for an extended time duration. Lumbago is extremely hard to manage and there is still no cure. Surgery is advised as the last measure although it is usually unnecessary and rarely succeeds in offering long term relief. The objective of the study was to assess the role of individualized homoeopathic medicines in the cases of chronic lumbago by using oswestry disability index. Study Design is Prospective Observational Study. Methodology: 44 cases of chronic lumbago were treated with Individualized Homoeopathic medicines which were prescribed on the basis of totality of the symptoms. Dose and potency selection was done according to the guidelines given by Dr. Hahnemann in the 5th edition of Organon of medicine. Follow ups of the cases were taken at an interval of 15 days upto 3 months with minimum 6 follow ups. The treatment outcome was assessed by using Oswestry Disability Index after three months of treatment. Results: Out of 44 patients maximum patients showed Improvement (n=35; 79.54%) followed by Status Quo (n=8; 18.18%) and Worse (n=1; 2.27%). Maximum patients were found to be in the age group of 36 to 45 years (n=13; 29.54%) and females (n=30; 68.19%) were more commonly affected than males (n=14; 31.81%). Frequently prescribed medicines were Natrium Muriaticum, Phosphorus and Lycopodium Clavatum. Paired t-test was conducted on the Oswestry Disability Index. The result showed that p value is < 0.05 & value of t (15.115) is greater than the tabulated value in t-table at df = 43 (2.02) which was statistically significant. Conclusion: Homoeopathic medicines were effective in treating Chronic lumbago.